2020
DOI: 10.1158/0008-5472.can-19-1633
|View full text |Cite
|
Sign up to set email alerts
|

Combined MEK and PI3K/p110β Inhibition as a Novel Targeted Therapy for Malignant Mesothelioma Displaying Sarcomatoid Features

Abstract: Among malignant mesotheliomas (MM), the sarcomatoid subtype is associated with higher chemoresistance and worst survival. Due to its low incidence, there has been little progress in the knowledge of the molecular mechanisms associated with sarcomatoid MM, which might help to define novel therapeutic targets. In this work, we show that loss of PTEN expression is frequent in human sarcomatoid MM and PTEN expression levels are lower in sarcomatoid MM than in the biphasic and epithelioid subtypes. Combined Pten an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
16
1
Order By: Relevance
“…Indeed, ROS can directly lead to the inactivation of PTEN, a lipid phosphatase involved in the negative regulation of this pathway, through the oxidation of its cysteine residues [20]. Recently, loss of PTEN expression has been reported in a high percentage of human sarcomatoid MPM as compared with other subtypes [15]. In addition, components of the PI3K/AKT/mTOR pathway have been found to be deregulated in MPM, in particular mutations in the catalytic subunit of PI3K have been frequently detected in MPM patients and associated to disease progression [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ROS can directly lead to the inactivation of PTEN, a lipid phosphatase involved in the negative regulation of this pathway, through the oxidation of its cysteine residues [20]. Recently, loss of PTEN expression has been reported in a high percentage of human sarcomatoid MPM as compared with other subtypes [15]. In addition, components of the PI3K/AKT/mTOR pathway have been found to be deregulated in MPM, in particular mutations in the catalytic subunit of PI3K have been frequently detected in MPM patients and associated to disease progression [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…These effects were observed under both normoxic and hypoxic conditions. It is worth noting that both MSTO-211H and H2052 cells were positive for PTEN protein (a negative regulator of AKT activation frequently lost in tumors including MPM [15]) and its expression was not affected by the drug treatments.…”
Section: The Combined Treatment With Cdk4/6 and Pi3k/mtor Inhibitors mentioning
confidence: 99%
“…Our research also shows that MEK2 also plays an important role in the proliferation and migration of ccRCC cells. Studies have reported that treatment of cells with AZD6244 for a short time reduced the phosphorylation level of MEK1/2 instead of regulating the protein expression of MEK1/2 [ 34 , 35 ]. However, our results showed that AZD6244 decreased MEK2 protein level (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in AS events are frequently observed in cancer and are beginning to be recognized as critical signatures of tumor development, differentiation and treatment [ 14 ]. MM is an aggressive tumor with high chemoresistance and poor survival [ 34 ]. Due to the low incidence of MM, there has been little progress in the knowledge of the molecular mechanisms associated with MM.…”
Section: Discussionmentioning
confidence: 99%